Performance Measurement and Information Production - Christian Laux; Volker Laux (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2004)
When performance measures are used for evaluation purposes, agents have some incentives to learn how their actions affect these measures. We show that the use of imperfect performance measures can cause an agent to devote too many resources (too much effort) to acquiring information. Doing so can be costly to the principal because the agent can use information to game the performance measure to the detriment of the principal. We analyze the impact of endogenous information acquisition on the optimal incentive strength and the quality of the performance measure used.
Keywords: 330; Informationsverhalten; Betriebliche Kennzahl; Agency Theory; Anreizvertrag; Theorie